Transcriptomic profiling of cytomegalovirus infection in cardiac transplantation: proof-of-concept for a new strategy in tissue markers application - Barison, Ilaria; Perazzolo, Diego; Castellani, Chiara; Giarraputo, Alessia; Rossi, Elisabetta; Vedovelli, Luca; Minuzzo, Sonia Anna; Tessari, Chiara; Pradegan, Nicola; Toscano, Giuseppe; Tona, Francesco; Basso, Cristina; et al. (Frontiers in Immunology, 2025)
BackgroundCytomegalovirus (CMV) infection is a relevant threat to heart-transplanted patients during the first year after surgery, leading to increased morbidity and, in some cases, mortality. This proof-of-concept study aims to assess the transcriptomic profile of CMV infection in cardiac transplanted patients as a new diagnostic approach to discriminate infection and Acute Cellular Rejection (ACR) on EMB specimens.MethodsWe performed a microarray-based messenger RNA (mRNA) and micro-RNA (miRNA) profiling. We analyzed three patient groups in the setting of CMV viremia and inflammatory infiltrate: a control group (n=5), an ACR group (n=5), and an infection group (n=6). Differentially expressed mRNA and miRNA were further investigated through bioinformatic pathway analysis.ResultsFocusing on infection vs rejection comparison, we investigated the role of the 18 differentially expressed mRNAs and the 12 miRNAs with the most significative p-value (gene level fold change, FC <-2 or >2, p-value <0.05). Based on the bioinformatic analysis, we explored the regulatory effects of these miRNAs on the mRNA pathways independently identified in the same samples. The results showed that two genes, IL7R and GZMK (-38.63 and -3.15 FC, respectively), and two miRNAs, mir-93-5p and mir-345-5p (-2.63 and -2.18 FC, respectively), are differentially expressed in infection and can be exploited to differentiate CMV-positive from ACR-positive EMB specimens, reaching an AUC of 0.87 and an accuracy of 91% at cross-validation.ConclusionsWe have identified a distinctive combined molecular profile of mRNAs and miRNAs for infection in post-cardiac transplant follow-up. Based on IL7R, GZMK, mir-93-5p, and mir-345-5p we suggest a novel possible workflow to distinguish infection, where those markers are downregulated, from rejection, where they are overexpressed, on EMB specimens. This analysis showed good accuracy and promising predictive performance. The future combined analysis of these genes and these miRNAs through user-friendly techniques, such as quantitative PCR, could reduce turn-around time and improve our diagnostic power for distinguishing CMV infection from ACR in EMB specimens.